2004
DOI: 10.1128/jvi.78.17.9458-9473.2004
|View full text |Cite
|
Sign up to set email alerts
|

Host Cell Gene Expression during Human Immunodeficiency Virus Type 1 Latency and Reactivation and Effects of Targeting Genes That Are Differentially Expressed in Viral Latency

Abstract: The existence of reservoirs of cells latently infected with human immunodeficiency virus (HIV) is a major obstacle to the elimination of HIV infection. We studied the changes in cellular gene expression that accompany the reactivation and completion of the lytic viral cycle in cell lines chronically infected with HIV-1. We found that several genes exhibited altered expression in the chronically infected cells compared to the uninfected parental cells prior to induction into lytic replication. A number of gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 72 publications
(77 reference statements)
5
96
0
Order By: Relevance
“…4). The chemopreventative agent Resveratrol inhibits AP-1 transcriptional activity 60 and depletes the HIV-1 reservoir in infected cells; 61 we show that Resveratrol inhibits HIV-1's ability to induce DNMT1 expression. To our knowledge, this is the first example that Resveratrol can be used to block the induction of DNMT1 which has implications as a chemopreventative agent through the inhibition of inappropriate DNMT1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…4). The chemopreventative agent Resveratrol inhibits AP-1 transcriptional activity 60 and depletes the HIV-1 reservoir in infected cells; 61 we show that Resveratrol inhibits HIV-1's ability to induce DNMT1 expression. To our knowledge, this is the first example that Resveratrol can be used to block the induction of DNMT1 which has implications as a chemopreventative agent through the inhibition of inappropriate DNMT1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In a transcriptome study in cell lines latently infected with HIV, Cdc42 expression was found to be downregulated, which perhaps may be involved in cellular maintenance of latency. 111 Overall, although there is considerable evidence that Rho GTPase signaling may be involved in regulating viral gene expression during productive viral replication for different viruses, the potential contribution of Rho GTPase signaling during viral latency is less well documented thus far.…”
Section: Gene Expression and Latencymentioning
confidence: 99%
“…It was shown that the latent reservoir was still present in HIV-1 patients after long-term ART and simultaneous VA treatment for neurological and psychiatric disorders (12,13). Other small molecules, such as suberoylanilide hydroxamic acid (SAHA) (14 -16), resveratrol (17), and prostratin (18,19), have been proposed as potential agents for the disruption of HIV latent infection. Prostratin induces the NF-B activation pathway (20,21), which puts into question its use in clinical studies because abnormal NF-B signaling has been related to the pathophysiology of cancer, inflammatory diseases, and neurodegenerative disorders (22)(23)(24)(25).…”
mentioning
confidence: 99%